Angular Approach Scanning Ion Conductance Microscopy - Shevchuk, A; Tokar, S; Gopal, S; Sanchez-Alonso, J; Tarasov, A; Vélez-Ortega, A; Chiappini, C; Rorsman, P; Stevens, M; Gorelik, J; Frolenkov, G; Klenerman, D; et al. (Elsevier, 2016)
Scanning ion conductance microscopy (SICM) is a super-resolution live imaging technique that uses a glass nanopipette as an imaging probe to produce three-dimensional (3D) images of cell surface. SICM can be used to analyze cell morphology at nanoscale, follow membrane dynamics, precisely position an imaging nanopipette close to a structure of interest, and use it to obtain ion channel recordings or locally apply stimuli or drugs. Practical implementations of these SICM advantages, however, are often complicated due to the limitations of currently available SICM systems that inherited their design from other scanning probe microscopes in which the scan assembly is placed right above the specimen. Such arrangement makes the setting of optimal illumination necessary for phase contrast or the use of high magnification upright optics difficult. Here, we describe the designs that allow mounting SICM scan head on a standard patch-clamp micromanipulator and imaging the sample at an adjustable approach angle. This angle could be as shallow as the approach angle of a patch-clamp pipette between a water immersion objective and the specimen. Using this angular approach SICM, we obtained topographical images of cells grown on nontransparent nanoneedle arrays, of islets of Langerhans, and of hippocampal neurons under upright optical microscope. We also imaged previously inaccessible areas of cells such as the side surfaces of the hair cell stereocilia and the intercalated disks of isolated cardiac myocytes, and performed targeted patch-clamp recordings from the latter. Thus, our new, to our knowledge, angular approach SICM allows imaging of living cells on nontransparent substrates and a seamless integration with most patch-clamp setups on either inverted or upright microscopes, which would facilitate research in cell biophysics and physiology.